2023
DOI: 10.3390/genes14010136
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in Human Face Prediction Using DNA

Abstract: The rapid improvements in identifying the genetic factors contributing to facial morphology have enabled the early identification of craniofacial syndromes. Similarly, this technology can be vital in forensic cases involving human identification from biological traces or human remains, especially when reference samples are not available in the deoxyribose nucleic acid (DNA) database. This review summarizes the currently used methods for predicting human phenotypes such as age, ancestry, pigmentation, and facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 187 publications
1
3
0
Order By: Relevance
“…3; lower ranks reflect superior performance). These mean ranks are consistent with the upper terminus of the overall blind search R 50 mean rank range (8)(9)(10)(11)(12)(13)(14)(15) reported earlier [13]. The overall blind search R 25 and R 10 mean ranks (6-12 and 3-6, respectively) observed in this study were similarly consistent with the mean ranks (6-12 and 3-4, respectively) reported by the authors for corresponding rank classes [13].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3; lower ranks reflect superior performance). These mean ranks are consistent with the upper terminus of the overall blind search R 50 mean rank range (8)(9)(10)(11)(12)(13)(14)(15) reported earlier [13]. The overall blind search R 25 and R 10 mean ranks (6-12 and 3-6, respectively) observed in this study were similarly consistent with the mean ranks (6-12 and 3-4, respectively) reported by the authors for corresponding rank classes [13].…”
Section: Resultssupporting
confidence: 91%
“…Accurate sex estimation, for example, declines to ≈90-92% when only the cranium is examined [7,13]. Genomic and proteomic methods of sex determination are highly successful, even from degraded and archaeological bones [8], and genetic testing offers relatively crude estimations of ethnicity [14] as well as predictions of facial and other phenotypic features [15], but resources do not always permit their use. When a complete set of remains is unavailable, indeterminate estimations and errors may occur, a problematic situation that may falsely exclude individuals from a short list of potential candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists generally acknowledge that they are currently only scratching the surface in terms of the ‘genetic architecture of the face’, which is known to be utterly complex (e.g. Alshehhi et al, 2023; Naqvi et al, 2022; Sero et al, 2019). The hope however is that, even in its current state, DNA phenotyping could be useful in forensic practice to narrow pools of potential suspects (Naqvi et al, 2022).…”
Section: Generous Methods and Affinity Conceptsmentioning
confidence: 99%
“…The FDP tool consists of two components: (1) a multiplex genotyping tool to analyze several DNA markers, and (2) a validated prediction model to obtain a high probability of appearance prediction. Moreover, the age estimation of the sample can also be obtained from epigenetic data by analysis of specific CpG sites [16,17], as can the identification of craniofacial features based on genetic variation [18]. However, there are some limitations to the recent and earlier studies on forensically DNA-based appearance, ancestry, and age prediction.…”
Section: Introductionmentioning
confidence: 99%